PSIKOLOGI DAN PASTORAL KONSELING DALAM PENDIDIKAN ORANG DEWASA - Raintung, Agnes Beatrix Jackline; Lahose, Geri Harkel; Manoppo, Laima Melanny; Muliku, Efron (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
This article discusses the important role of developmental psychology in adult education, especially in the context of Christian education. Understanding the characteristics of adult development, such as cognitive, social, emotional, and spiritual development, is essential for Christian educators to design effective and relevant educational programs. This article describes several principles of adult education based on developmental psychology, such as adult-centered learning, relevant learning, collaborative learning, and sustainable learning. Furthermore, this article discusses how the principles of Christian education can be integrated with developmental psychology to create holistic and meaningful educational programs for adults. The research method used is literature with data collection techniques that identify sources relevant to the research topic. This can be books, journal articles, research reports, theses, dissertations and other documents that can be accessed in the library or online. Data Collection: After identifying relevant sources, the researcher collects data by reading and recording important information that is in accordance with the research objectives. Data Classification: The data that has been collected is then classified based on certain themes or topics to make the analysis process easier. Data Analysis: Data that has been classified is then explained to find patterns, concepts, or theories that are relevant to the research topic. This analysis can be descriptive analysis, comparative analysis, or critical analysis. Synthesis and Interpretation: The results of data analysis are then synthesized and interpreted to provide a deeper understanding of the research topic. Researchers connect the findings obtained with existing theories or concepts to answer research questions.